Acting Performance Evaluation Governor of Aceh in 2022 Based on Key Performance Indicators (KPIs) : Key Performance Indicators (KPIs), Acting Governor of Aceh: Achmad Marzuki, Strategic Policy, Strategic Program - Ali, Chaidir; Rahmawati, Dian Eka (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2024)
This research seeks to prove the hypothesis regarding the performance of the Acting Governor of Aceh using the framework of Key Performance Indicators. The measurement variables for the Main Performance Indicators are Adaptability to Change, Financial Management, Infrastructure Development, Public Service, and Stakeholder Satisfaction. Since June 2022, Aceh Province has become a new chapter of leadership after the Helsinki MoU from the Military, this is in contrast to the message of the struggle, that the Military has a place in the hearts of the Acehnese people. So the presence of the military in the Aceh leadership system is interesting to study from its performance during its tenure. This research uses a quantitative descriptive method with data sources from questionnaires via Google Forms with 100 respondents, and data processing is carried out using Smart PLS software. The results of this research show an R Square value of 0.705, thus it can be concluded that 70.5% of the variation in the performance of the Acting Governor of Aceh can be explained by the independent variables in the regression model. R Square identifies quality in the form of strong/medium/weak categories. Several KPI variables that have a significant influence on the performance of the Acting Governor of Aceh are financial management, public service, and stakeholder satisfaction, with P Values ​​of 0.011, 0.020, and 0.035, with these results the performance of the Acting Governor of Aceh was successful in achieving the Main Performance Indicators. Meanwhile, the variables adaptability to change and infrastructure development with P values ​​of 0.405 and 0.343 do not have a significant effect on the performance of the Acting Governor of Aceh on the KPI Indicators.